LABOUR ROOM: UNVEILING THE COMPLEXITIES OF MOTHERHOOD AND MARGINALIZATION IN WOMEN'S THEATRE - Vineetha Krishnan (ShodhKosh: Journal of Visual and Performing Arts, 2022)
K. V. Sreeja’s Labour Room (2003) offers a poignant exploration of the complexities surrounding childbirth and motherhood, addressing themes of gender, class, and societal expectations. The play critiques romanticized myths of motherhood while spotlighting the physical, emotional, and social challenges women endure. Through representative characters, it highlights diverse experiences shaped by socio-economic and cultural factors, emphasizing the material realities of women’s bodies. The play also critiques the patriarchal gaze, exploring trauma, resilience, and solidarity among women. By portraying childbirth as a deeply individual yet universally impactful experience, Labour Room challenges dominant narratives, fostering awareness and advocating for a supportive, egalitarian society.